COMPARISON OF THE MFEP METHOD WITH THE SAW METHOD TO DETERMINE POTENTIAL RECIPIENTS OF THE FAMILY HOPE PROGRAM (PKH) ASSISTANCE - Oktarina Rina (TECHSI - Jurnal Teknik Informatika, 2025)
Family Hope Program Assistance (PKH) is a conditional cash transfer program in an effort to improve the quality of human resources launched by the government in 2007. Koto Balingka Subdistrict is one of the sub-districts in West Pasaman Regency, West Sumatra, where most of the population is recipients of PKH Assistance. This study intend to create an application that can help PKH assistance assistants in Koto Balingka District to determine families who are entitled to PKH assistance using the Decision Support System (SPK). PHP is used as the programming language in this study and MySQL as the database. This study also intend to compare the final results of the ranking of the MFEP method and the SAW method. The data sample used in this study was 1000 actual data from residents of Koto Balingka District, West Pasaman Regency, where there were 715 families who were eligible to receive PKH assistance while 285 families were not eligible. The criteria used are children aged 0-6 years, SD/MI, SMP/MTS, SMA/MA, elderly/severe disabilities, income, type of house floor, type of house wall, type of roof and water source with a total weight value of 1. The results of the calculation using the MFEP method were 660 eligible PKH beneficiaries and 340 ineligible recipients of PKH assistance, the percentage of conformity with the test data was 93.5%. Mrs. Siti Khodijah ranked first who deserved to receive PKH assistance using the MFEP method with a final score of 1, while the results of the calculation of the SAW method who deserved to receive PKH assistance were 128 people and 872 people who were not eligible to receive PKH assistance, the percentage of conformity with the test data was 26, 5%. Mrs. Marwah Syafwani was the first rank eligible to receive PKH assistance using the SAW method with a final score of 0.925.